A Institucionalização da gestão ambiental nas universidades federais brasileiras - Dantas, Cleide Vasconcelos (2001)
In view of the growing awareness of the importance of environmental conservation, the Brazilian federal government has determined the preparation and implementation of Sustainable Logistics Management Plans (PLS) in public administration, through Decree No. 7,746 / 2012. However, the recurring allegations of difficulties in making environmental management a reality, justified this study, which aims to analyze the institutionalization of environmental management in Brazilian Federal Universities. For that, a research of an applied and descriptive nature was carried out, with qualitative and quantitative approaches, delineated as documentary research, in case study in a temporal span of five years. There was a strong institutionalization of environmental initiatives in teaching, research and extension. However, it was found that the PLS, or Environmental Management Systems (EMS) created by the Federal Universities lack an institutional environmental policy that precedes them, giving them legal basis and the necessary institutional attention. It is suggested, for future research, to investigate the insertion of contents of Environmental Education in the curricular grades of undergraduate courses offered by the UFs in all areas of knowledge.